2016
DOI: 10.1016/j.jconrel.2016.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Coated minispheres of salmon calcitonin target rat intestinal regions to achieve systemic bioavailability: Comparison between intestinal instillation and oral gavage

Abstract: Achieving oral peptide delivery is an elusive challenge. Emulsion-based minispheres of salmon calcitonin (sCT) were synthesized using single multiple pill (SmPill ® ) technology incorporating the permeation enhancers (PEs): sodium taurodeoxycholate (NaTDC), sodium caprate (C 10 ), or coco-glucoside (CG), or the pH acidifier, citric acid (CA). Minispheres were coated with an outer layer of Eudragit ® L30 D-55 (designed for jejunal release) or Surelease ® /Pectin (designed for colonic release). The process was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In situ rat jejunal instillations were carried out to assess the lyophilised encapsulator-synthesised insulin-dWPI beads. The method was according to previous descriptions [ 33 , 34 ], but with modifications to accommodate the beads. A midline laparotomy was performed under anaesthesia and the jejunum was identified.…”
Section: Methodsmentioning
confidence: 99%
“…In situ rat jejunal instillations were carried out to assess the lyophilised encapsulator-synthesised insulin-dWPI beads. The method was according to previous descriptions [ 33 , 34 ], but with modifications to accommodate the beads. A midline laparotomy was performed under anaesthesia and the jejunum was identified.…”
Section: Methodsmentioning
confidence: 99%
“…Its mechanism of action was envisaged as a combination of i) maintenance of insulin in its monomeric active form; ii) paracellular permeation enhancement, demonstrated in Caco‐2 cells; iii) inhibition of proteolytic enzymes; and iv) mucus layer thinning. Also worth mentioning is the strategy presented as single multiple pill (SmPill),43 consisting of enteric‐coated emulsion‐based minispheres incorporating several permeation enhancers.…”
Section: Recent Advances In Preclinical Stage On Systemic Delivery Ofmentioning
confidence: 99%
“…The images were recorded at the tie intervals of 4, 8, 16, and 28 h using an online computer system, stored on magnetic disk, and analyzed to determine the distribution of activity in the stomach and intestine and colonic region. [12] Pharmacokinetic studies…”
Section: Stability Studiesmentioning
confidence: 99%
“…Reduction in size of capsule indicated that the capsules were broken down and released the drug in colon at 28 th h. The results are in accordance with the fact that the optimized formulation could be targeted specifically to the colon, without any premature drug release in the stomach and small intestine. [12]…”
Section: Stability Studiesmentioning
confidence: 99%